2022
DOI: 10.3389/fnut.2022.906646
|View full text |Cite|
|
Sign up to set email alerts
|

Financial Wellbeing and Quality of Life Among a Sample of the Lebanese Population: The Mediating Effect of Food Insecurity

Abstract: BackgroundLebanon is undergoing multiple overlapping crises, affecting the food security, financial well-being, and quality of life (QOL) of its residents.ObjectiveThe primary objective was to assess the food insecurity (FI) status of a sample of the Lebanese population. The second objective was to explore factors related to QOL parameters and evaluate the mediating effect of food security between financial well-being and QOL.MethodsThe study was cross-sectional and enrolled 412 participants recruited online u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Gender bias was also observed, as about 80% of the respondents were women. There is a greater predisposition in the female public, also observed in other studies [80][81][82][83], to collaborate with these types of studies, and perhaps there is also a greater concern and sensitivity to nutrition and health issues among women than among their male counterparts. This notwithstanding, due to an awareness of the importance of achieving a balanced sample, an additional effort was made to reach more men as participants in the study, finally achieving a sample of 3682 men.…”
Section: Strengths and Limitationsmentioning
confidence: 82%
“…Gender bias was also observed, as about 80% of the respondents were women. There is a greater predisposition in the female public, also observed in other studies [80][81][82][83], to collaborate with these types of studies, and perhaps there is also a greater concern and sensitivity to nutrition and health issues among women than among their male counterparts. This notwithstanding, due to an awareness of the importance of achieving a balanced sample, an additional effort was made to reach more men as participants in the study, finally achieving a sample of 3682 men.…”
Section: Strengths and Limitationsmentioning
confidence: 82%
“…Additionally, other studies may similarly investigate the long-term sustainability and effectiveness of financial aid interventions, aiming to understand if positive outcomes persist over time. In a previous study, there was an association between food insecurity, financial well-being, and quality of life [ 14 ]. Previous studies aligned that both subjectively and objectively measured financial stress are inversely associated with good self-reported health and quality of life and positively associated with self-reported depression among the elderly [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rose-Ackerman and Palifka (2016) observed correlations between quality of life and the propensity for corruption, while Ma et al (2022) found that the more satisfied a person is with their living conditions, the less likely they are to think about offering a bribe. Although one might state that quality of life and financial insecurity are correlated (Karam et al, 2022), the perceived quality of life has many more dimensions than just financial (Felce and Perry, 1995;Haraldstad et al, 2019;Costa et al, 2021), most of which are of a subjective nature and cannot be assessed by hard data and metrics (Ridzi et al, 2020). It is even suggested by Mamirkulova et al (2020) that perceived quality of life is more important in shaping a person's well-being than anything that can be measured.…”
Section: Hypotheses Buildingmentioning
confidence: 99%